Maximizing ESG practices on firm performance evidence from 45 mining companies listed on IDX - Dinda Purwitasari; Sumardi Sumardi; Risma Wulandari; Filda Ristin Anggraini (Enrichment : Journal of Management, 2023)
The purpose of this research is to examine the impact of environmental, social, and governance (ESG) disclosures on corporate performance, utilizing control variables such as financial leverage and total assets. This study's variables include the dependent variable (operational and financial performance), the independent variable (ESG disclosure), and the control variable (financial leverage). This study uses quantitative research methods. This study's population consists of mining businesses listed on the IDX. Purposive sampling was used to collect data. The sample collected using the purposive sampling approach consisted of 45 mining enterprises. Multiple regression analysis was employed in this investigation, which was conducted using SPSS version 25 software. According to the findings of this study, ESG disclosure has a positive and significant impact on operational and financial performance.